Ceramides and Sphingosino-1-Phosphate in Obesity - Juchnicka, Ilona; Kuźmicki, Mariusz; Szamatowicz, Jacek (Frontiers in Endocrinology, 2021)
Obesity is a growing worldwide problem, especially in developed countries. This disease adversely affects the quality of life and notably contributes to the development of type 2 diabetes, metabolic syndrome and cardiovascular disorders. It is characterised by excessive lipids accumulation in the subcutaneous and visceral adipose tissue. Considering the secretory function of adipose tissue, this leads to impaired adipokines and cytokines release. Changes in adipose tissue metabolism result in chronic inflammation, pancreatic islets dysfunction and peripheral insulin resistance. In addition to saturating various adipocytes, excess lipids are deposited into non-adipose peripheral tissues, which disturbs cell metabolism and causes a harmful effect known as lipotoxicity. Fatty acids are metabolised into bioactive lipids such as ceramides, from which sphingolipids are formed. Ceramides and sphingosine-1-phosphate (S1P) are involved in intracellular signalling, cell proliferation, migration and apoptosis. Studies demonstrate that bioactive lipids have a crucial role in regulating insulin signalling pathways, glucose homeostasis and β cell death. Data suggests that ceramides may have an opposite cellular effect than S1P; however, the role of S1P remains controversial. This review summarises the available data on ceramide and sphingolipid metabolism and their role in obesity.